Mencari Badan Publik:Refleksi bagi Rehabilitasi Arti Pembangunan - Herry-Priyono, B. (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Having examining three possible explanations why the notion of development has lost its significant, the author proposes to rehabilitate it by reinventing the notion of public agency. The notion of development lost its significance due to the absence of steering agency, namely the absence of institution to consciously manage private character of political economic performance in the pursuit of common good. Government and public policy has lost its nature as public agency, and rehabilitate the notion of government to restore the sense of public within it.